Stabilization of water in oil in water (W/O/W) emulsion using whey protein isolate-conjugated durian seed gum: enhancement of interfacial activity through conjugation process - Amid, Bahareh Tabatabaee; Mirhosseini, Hamed (Elsevier, 2014)
The present work was conducted to investigate the effect of purification and conjugation processes on functional properties of durian seed gum (DSG) used for stabilization of water in oil in water (W/O/W) emulsion. Whey protein isolate (WPI) was conjugated to durian seed gum through the covalent linkage. In order to prepare WPI–DSG conjugate, covalent linkage of whey protein isolate to durian seed gum was obtained by Maillard reaction induced by heating at 60 °C and 80% (±1%) relative humidity. SDS-polyacrylamide gel electrophoresis was used to test the formation of the covalent linkage between whey protein isolate and durian seed gum after conjugation process. In this study, W/O/W stabilized by WPI-conjugated DSG A showed the highest interface activity and lowest creaming layer among all prepared emulsions. This indicated that the partial conjugation of WPI to DSG significantly improved its functional characteristics in W/O/W emulsion. The addition of WPI-conjugated DSG to W/O/W emulsion increased the viscosity more than non-conjugated durian seed gum (or control). This might be due to possible increment of the molecular weight after linking the protein fraction to the structure of durian seed gum through the conjugation process.